Guidelines for Argentine Theatre in the Era of the Masses: Theatre, People, and Public Formation (Anclajes, 2025)
In the early decades of the 20th century, the dramatic scene became a privileged platform where artistic practices characterized by their experimental and popular nature circulated. It reveals how the spoken word became a point of contention between the desired harmony of Enlightened aesthetic expressions and the dissonant quality of the people's stage proposals. Through publications and the press of the time, the process by which the consolidation of national theater involved the intervention of certain agents to shape the use of vocal delivery in dramatic texts is analyzed. Comic monologues and poetic declamation are genres in which orality played a central role. The emergence of entertainment culture introduced a new way of circulating and disseminating these stage practices, challenging any form of regulation by cultural agents striving to stabilize the use of spoken language. Thus, theater functioned as a laboratory where artistic expressions negotiated the establishment of a national language.
Keywords: Theater; Argentine Literature; Cultural History; 20th Century; Argentina